The mitochondrial complex I proteins of Candida albicans moderate phagocytosis and the production of pro‐inflammatory cytokines in murine macrophages and dendritic cells. Issue 11 (8th October 2022) - She, Xiaodong; Zhang, Pengyi; Shi, Dongmei; Peng, Jingwen; Wang, Qiong; Meng, Xiangjing; Jiang, Yong; Calderone, Richard; Bellanti, Joseph A.; Liu, Weida; Li, Dongmei
Abstract: Loss of respiratory functions impairs Candida albicans colonization of host tissues and virulence in a murine model of candidiasis. Furthermore, it is known that respiratory inhibitors decrease mannan synthesis and glucan exposure and thereby promotes phagocytosis. To understand the impact of respiratory proteins of C. albicans on host innate immunity, we characterized cell wall defects in three mitochondrial complex I (CI) null mutants ( nuo1Δ, nuo2Δ and ndh51Δ ) and in one CI regulator mutant ( goa1 Δ), and we studied the corresponding effects of these mutants on phagocytosis, neutrophil killing and cytokine production by dendritic cells (DCs). We find that reductions of phosphopeptidomannan (PPM) in goa1Δ, nuo1Δ and phospholipomannan (PLM) in nuo2Δ lead to reductions of IL‐2, IL‐4, and IL‐10 but increase of TNF‐α in infected DCs. While PPM loss is a consequence of a reduced phospho‐Cek1/2 MAPK that failed to promote phagocytosis and IL‐22 production in goa1Δ and nuo1Δ, a 30% glucan reduction and a defective Mek1 MAPK response in ndh51Δ lead to only minor changes in phagocytosis and cytokine production. Glucan exposure and PLM abundance seem to remain sufficient to opsonize neutrophil killing perhaps via humoral immunity. The diversity of immune phenotypes in these mutants possessing divergent cell wall defects is further supported by their transcriptional profiles in each infected murine macrophage scenario . Since metabolic processes, oxidative stress‐induced senescence, and apoptosis are differently affected in these scenarios, we speculate that during the early stages of infection, host immune cells coordinate their bioactivities based upon a mixture of signals generated during host‐fungi interactions.